Instructional design : system strategies - Ledford, Bruce R.; Sleeman, Phillip J. (Emerald Publishing Limited : Information Age Pub., 2002)
A demonstration of instructional design, from the point of view of what the learner is going to do. The chapters examine the instructional design process; perception and visual literacy - learner analysis; layout and design; the World Wide Web; and e-learning.
Keywords: Instructional systems -- United States -- Design.; Educational technology -- United States.; Education -- General.; Educational: Design and technology.; Education.; elektronické knihy; electronic books